Respiratory Modulation Of Premotor Cardiac Vagal Neurons In The Brainstem - Dergacheva, Olga (2010)
The respiratory and cardiovascular systems are highly intertwined, both anatomically and physiologically. Respiratory and cardiovascular neurons are often co-localized in the same brainstem regions, and this is particularly evident in the ventral medulla which contains pre-sympathetic neurons in the rostral ventrolateral medulla, premotor parasympathetic cardioinhibitory neurons in the nucleus ambiguus, and the ventral respiratory group, which includes the pre-Botzinger complex. Anatomical studies of respiratory and cardiovascular neurons have demonstrated that many of these neurons have projections and axon collateral processes which extend into their neighboring cardiorespiratory regions providing an anatomical substrate for cardiorespiratory interactions. As other reports in this Special Issue of Respiratory Physiology & Neurobiology focus on interactions between the respiratory network and baroreceptors, neurons in the nucleus tractus solitarius, presympathetic neurons and sympathetic activity, this report will focus on the respiratory modulation of parasympathetic activity and the neurons that generate parasympathetic activity to the heart, cardiac vagal neurons.